(untitled) (Research, Society and Development, 2020)
To demonstrate the link between loss of sense of life with depression and suicide in migrants, an epistemological path under the aegis of Logotherapy is followed. This research is justified to the extent that there are points of contact between depression and suicide in groups of people living in displacement and migration conditions. The object of this study is the absence of meaning of life as a predictive factor of depressive and suicidal symptoms in migrants. The origin of many of the threats to health are rooted in emotions and sufferings resulting from frustrations and hopelessness, so this paper has as objective to: analyze the thought about the meaninglessness of life present in the history of migrants, to draw elements that link depressive states and suicide. Study developed based on the deductive method, using bibliographic-documentary research. As a result it is expected to present the existing relationship rescue of the meaning of life as a preventive element of suicide.